To determine the value of \( c \) that would make the expression \( x^2 - 14x + c \) a perfect square trinomial, we can use the method of completing the square.
A perfect square trinomial can be expressed in the form \( (x - a)^2 = x^2 - 2ax + a^2 \).
In our case, we have:
\[ x^2 - 14x + c \]
Here, the coefficient of \( x \) is \(-14\). To find the value of \( c \) that makes this a perfect square, we take half of \(-14\) and square it:
-
Calculate half of \(-14\): \[ -\frac{14}{2} = -7 \]
-
Now square that value: \[ (-7)^2 = 49 \]
Thus, if \( c = 49 \), the expression \( x^2 - 14x + c \) becomes a perfect square trinomial:
\[ x^2 - 14x + 49 = (x - 7)^2 \]
Now, we have the equation:
\[ x^2 - 14x + 49 = 13 \]
Therefore, the value of \( c \) that would make the left-hand side a perfect square trinomial is:
\[ \boxed{49} \]